Pengaruh Kepemimpinan, Motivasi, dan Disiplin Kerja Terhadap Kinerja Pegawai - Riska Aryuni (Jurnal Ilmiah Multidisiplin Amsir, 2023)
The purpose of this study is to know and analyze the influence of leadership, motivation, and work discipline on the performance of employees of industry and commerce of gowa regency and analyze the factors that have dominant influence on employee performance. This research is carried out in the Department of Industry and trade of gowa regency using a sample of 53 respondents. Data analysis used is descriptive to explain the characteristics of respondents and description of research variables. Furthermore, quantitative data is analyzed by multiple regression analysis tools through Statistical Package for Social Science (SPSS) program to know information about the influence of leadership factor, motivation and work discipline, on employee performance either simultaneously or partially. The results of this study indicate that simultaneously all the independent variables studied have a positive effect on the performance of employees of industry and commerce of gowa regency, and the factors that have dominant influence on the performance of employees of Industry and Trade Office of gowa regency is the motivation factor. Based on the results of the research, recommendations can be given that is to improve the performance of employees at the Department of Industry and trade gowa district is needed leadership, motivation, discipline work.